A study of Ni–P electroless coating modified by rare earth oxide (La2O3, Y2O3 and Ce2O3) on pre-phosphorized zirconium alloy. Issue 1 (4th April 2023) - Cheng, Wenqin; Wen, Pengcheng; Wang, Tianyi; Yu, Hongyan; Jiang, Mingyan; Wen, Haiyan; Wang, Bin
Abstract: Electroless Ni–P coatings are successfully deposited on the surface of pre-phosphorized zirconium alloy from plating baths containing various concentrations of rare earth oxide (Re Y2 O3, Ce2 O3 and La2 O3 ). The surface morphology, elementary composition, and structure of coatings are characterized by scanning electron microscopy, energy dispersive X-ray spectrometer and X-ray diffraction, respectively. Gravimetrical method is used to calculate the deposition rate. Electrochemical corrosion resistance of coatings is analyzed using electrochemical workstation. Results revealed that a small amount addition of rare earth oxides does not change the original cauliflower-like morphology and amorphous structure of coatings. When the amount of addition is moderate, the deposition rate and microhardness increase with the increment of the amount of addition, while P content decreases. However, excessive addition can lead to poisoning of the plating bath. Electrochemical corrosion data indicates that the addition of rare earth oxide in the plating solution has little influence on the corrosion resistance of the coating.